Orthopedic Pathology in Children with Mucopolysaccharidosis Type I - Nato D. Vashakmadze; Leyla S. Namazova-Baranova; Anait K. Gevorkian; Ludmila M. Kuzenkova; Tatiana V. Podkletnova; Marina A. Babaykina; Anatoly B. Anikin; Galina B. Kuznetsova; Liliya A. Osipova; Konstantin V. Jerdev ("Paediatrician" Publishers LLC, 2016)
Mucopolysaccharidosis type I is inherited in an autosomal recessive manner and results from the defective activity of the enzyme alpha-L-iduronidase, which leads to the accumulation of glycosaminoglycans (mainly heparan and dermatan sulfate) in the lysosomes and further multiple organ dysfunction. This severe genetic progressive disease can be detected at an early age by skeletal deformities and phenotypic data. Early enzyme replacement therapy and/or bone marrow transplantation can slow down irreversible damages to various organs and systems or reduce their severity and improve the quality of life for a child.